Social Identity and Nature of Science Knowledge at the Undergraduate Level - Taylor, Liv; Sobhanzadeh, Mandana; Strzalkowski, Nicholas (Imagining SoTL, 2025)
Science literacy is essential for informed participation in modern society, and undergraduate education plays a critical role in fostering science literacy among science and non-science students. One important component of science literacy is understanding the nature of science (NOS), yet traditional NOS frameworks have been critiqued for oversimplifying scientific practice and neglecting its social and cultural dimensions. While social identity is known to influence student academic engagement and performance, little is known about how identity factors such as gender, age, program and level of study, being a visible minority, or parental education influences NOS beliefs. In this study, 272 undergraduate students from a Canadian liberal arts university completed an online questionnaire assessing NOS knowledge. Students generally demonstrated a solid understanding of NOS, though their comprehension of scientific methods is limited. No significant differences in NOS beliefs were found across social identity groups, but non-science majors were more likely to report uncertainty in their responses compared to science majors. These findings suggest that traditional NOS measures may fail to capture the nuanced ways that social identity shapes science understanding, emphasizing the need for justice-oriented approaches to NOS education.